The impact of probiotics on glycemic control during the first 3 months after sleeve gastrectomy: a prospective placebo‑controlled study - Natalia Mazek; Julia Młyńska; Ewelina Sosnowska-Turek; Paweł Lech; Natalia Dowgiałło-Gornowicz (Videosurgery and Other Miniinvasive Techniques)
Introduction: Sleeve gastrectomy (SG) is a safe metabolic and bariatric surgery but it often leads to postoperative gastrointestinal issues, such as constipation and bloating. The use of probiotics after SG seems to alleviate these symptoms.